Childbirth outcomes and ethnic disparities in Suriname: a nationwide registry-based study in a middle-income country - Verschueren, Kim J. C. (Reprod Health, 2020)
BACKGROUND: Our study aims to evaluate the current perinatal registry, analyze national childbirth outcomes and study ethnic disparities in middle-income country Suriname, South America. METHODS: A nationwide birth registry study was conducted in Suriname. Data were collected for 2016 and 2017 from the childbirth books of all five hospital maternity wards, covering 86% of all births in the country. Multinomial regression analyses were used to assess ethnic disparities in outcomes of maternal deaths, stillbirths, teenage pregnancy, cesarean delivery, low birth weight and preterm birth with Hindustani women as reference group. RESULTS: 18.290 women gave birth to 18.118 (98%) live born children in the five hospitals. Hospital-based maternal mortality ratio was 112 per 100.000 live births. Hospital-based late stillbirth rate was 16 per 1000 births. Stillbirth rate was highest among Maroon (African-descendent) women (25 per 1000 births, aOR 2.0 (95%CI 1.3–2.8) and lowest among Javanese women (6 stillbirths per 1000 births, aOR 0.5, 95%CI 0.2–1.2). Preterm birth and low birthweight occurred in 14 and 15% of all births. Teenage pregnancy accounted for 14% of all births and was higher in Maroon women (18%) compared to Hindustani women (10%, aOR 2.1, 95%CI 1.8–2.4). The national cesarean section rate was 24% and was lower in Maroon (17%) than in Hindustani (32%) women (aOR 0.5 (95%CI 0.5–0.6)). Cesarean section rates varied between the hospitals from 17 to 36%. CONCLUSION: This is the first nationwide comprehensive overview of maternal and perinatal health in a middle income country. Disaggregated perinatal health data in Suriname shows substantial inequities in outcomes by ethnicity which need to be targetted by health professionals, researchers and policy makers.